THE IMPORTANCE OF INTERACTIVE METHODS IN TEACHING UZBEK AS A SECOND LANGUAGE - Khabibullayeva Shoira (Western European Studies, 2025)
Teaching Uzbek as a second language requires modern pedagogical approaches that emphasize communication, learner engagement, and cultural awareness. Interactive teaching methods help students actively participate in the learning process, develop communicative competence, and apply linguistic knowledge in real-life contexts. This study examines the role and effectiveness of interactive methods in teaching Uzbek as a second language and provides practical insights for educators
Keywords: Uzbek language; second language acquisition; interactive methods